Tema . Tema . Theme . Тема - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. A psychologist, a lawyer, and a victim of sexual abuse by a family member discuss the problem of incest. Featured in the program: Loseva, Vera (Senior researcher at the Research Center for Family and Children of the Russian Academy of Education); D'iachenko, Anatolii (Candidate of Juridical Sciences) Contributors: List'ev, Vladislav Nikolayevich (Anchor) Series description: One of the first talk shows on Russian television. The program was produced by TV-company VID and broadcasted on the First Channel "Ostankino" from January 31, 1992. Initially, the program was hosted by Vladislav Listiev. Психолог, юрист и жертва сексуального насилия в семье обсуждают проблему инцеста. В программе участвуют: Лосева, Вера (Cтаршая научная сотрудница Исследовательского центра семьи и детства Российской Академии образования); Дьяченко, Анатолий (Кандидат юридических наук) Создатели: Листьев, Владислав Николаевич (Ведущий/Ведущая) Описание серии: Одно из первых российских ток-шоу. Передача производилась телекомпанией ВИД и выходила в эфир на 1-м канале Останкино с 31 января 1992 года. Первоначально программу вел Владислав Листьев.